A study on current practices, perspectives and challenges of non-governmental organisations (NGOs) towards corporate social responsibilities (CSR) in Klang Valley - Rozza Elena, Rosli (2019)
This paper aims to explore NGOs role in executing corporate social responsibility through their self-perception. The approach used for this study is qualitative approach with semi-structured interview as instrument where it allows the freedom of perspective exploration as well as substantially describe the phenomenon. In the course of this qualitative study, it has been found that five prominent issues are highlighted by the NGOs in term of current practices and challenges through their perspectives. The study confirms that there are lack of understanding of NGOs role from other stakeholder in CSR landscape which creates conflicts. NGOs weak branding exercise has also contribute to the majority of the challenges that they are currently facing like acquiring fund and ensuring sustainability of their organizations. The government lack of insights on the issues has further weaken the CSR practice. According to the NGOs, CSR is also seen by their corporate counterparts as branding and marketing exercise to gain favorable image from public. Corporate counterparts seen CSR a fraction of obligation to the community with benefits for themselves not only in term of public image but tax exemption as well which is the total opposite of NGOs goal which is to advance the social causes for the benefit of the community. Deep-seeded misunderstanding on the objective of CSR practice has impedes the CSR practice from becoming an effective tool of social development and sustainability. The study shows that all the stakeholders of CSR need to have a set of standards or framework on the practice of CSR and government as policy maker need to gear the stakeholders up with holistic guidelines through relevant and updated regulations as well as enforcement.